The relationship between voters' behavior and political utility among rice farmers. - Ilustre, Maria Christina G.; Tin, Jovy June E.; Tin, Jovy June E. (2003.)
This research looks into the dynamics and motivation behind the voting behavior of selected farmers in two barangays in Pototan. It compared the farmers' voting behavior from 1994-2001 local and national elections. Of the many factors that lead people to vote, this paper specifically looks into political utility. The relationship between voters' behavior and political utility was found out by outlining the reasons why farmers vote. The farmers were least motivated to vote by expectation of monetary or material reward in the form of personal assistance. Utilizing open-ended interviews to gather data, and frequencies, means and correlational tools, this study established whether farmers vote according to calculated political utility. The researchers found that there is no relationship between the voting behavior of farmers and their feeling of political utility.
Thesis (Undergraduate, Bachelor of Arts in Political Science) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Farmers, Rice -- Voters' Behavior